2021
DOI: 10.1080/20008198.2021.1968141
|View full text |Cite
|
Sign up to set email alerts
|

Helping patients connect remotely with their loved ones modulates distress in healthcare workers: tend-and-befriend hypothesis for COVID-19 front liners

Abstract: The no-visitor policies endorsed by healthcare organizations to limit COVID-19 virus risk exposure have unfortunately contributed to the isolation of patients further exacerbating distress in relatives and frontline healthcare workers. To contrast such effects, many healthcare institutions have adopted technology-based solutions helping patients and families communicate online through the aid of virtual devices. To date, no study has investigated whether facilitating patient-family videocalls would mitigate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Moreover, we discovered some differences in mental health between doctors and nurses, with nurses being more likely to experience fatigue, anxiety, and insomnia symptoms in the early pandemic period. Similarly, studies from other countries have revealed that the mental health burden on healthcare workers during the COVID-19 pandemic is significantly higher among nurses than doctors, owing to a greater exposure to both patients' and families' suffering and distress (28,29). More importantly, this survey showed that there were considerable disparities in the prevalence of fatigue, anxiety, and insomnia symptoms among healthcare professionals of different genders, with women scoring significantly higher than men.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, we discovered some differences in mental health between doctors and nurses, with nurses being more likely to experience fatigue, anxiety, and insomnia symptoms in the early pandemic period. Similarly, studies from other countries have revealed that the mental health burden on healthcare workers during the COVID-19 pandemic is significantly higher among nurses than doctors, owing to a greater exposure to both patients' and families' suffering and distress (28,29). More importantly, this survey showed that there were considerable disparities in the prevalence of fatigue, anxiety, and insomnia symptoms among healthcare professionals of different genders, with women scoring significantly higher than men.…”
Section: Discussionmentioning
confidence: 58%
“…Lastly, the Insomnia Severity Index (ISI), a self-report tool that assesses the intensity of insomnia during the previous 2 weeks, contains seven items with a total score ranging 0-28 (19). The corresponding relationship between the total score and severity of insomnia was normal (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe (22)(23)(24)(25)(26)(27)(28) insomnia.…”
Section: Fatigue Anxiety and Insomnia Symptomsmentioning
confidence: 99%
“…In line with previous studies [1][2][3], the more pronounced insecure attachment exhibited by nursing students may affect their forthcoming clinical practice both in terms of their role as caregivers and as members of interdisciplinary healthcare teams. It may also represent a potential disturbing factor in the development of effective relationships with patients and families [11]. However, these findings should be discussed in the light of the results obtained on the mentalization measure.…”
Section: Discussionmentioning
confidence: 99%
“…Among healthcare professions, nursing is perhaps the most demanding as it requires delivering compassionate care in often stressful and adverse conditions and to effectively navigate complex interpersonal relations with patients, families and other healthcare professionals [10,11]. If more insecurely attached individuals cope less well with stress, are tendentially ill-equipped in mentalization capacities that facilitate interpersonal relationships and are more prone to burnout, then adult attachment insecurities and poor mentalization capacity may be expected to predict burnout in nurse professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, emotional support was positively correlated with fear of death and negatively associated with neutral acceptance among the Norwegian respondents. Fino et al (2020Fino et al ( , 2021b emphasized that physical and social isolation precautions related to COVID-19 might result in increased fear and distress regarding the disease itself among people. Additionally, some studies showed that stress may increase one's likelihood of seeking emotional support (Joo et al, 2020).…”
Section: Agementioning
confidence: 99%